2019
DOI: 10.1186/s13104-019-4552-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of chronic undernutrition among under five children in Adama town, Central Ethiopia: a cross-sectional study design

Abstract: Objectives The purpose of this study was to assess the prevalence and factors associated with stunting among under five children in Adama town, Central Ethiopia, 2013. A community based cross sectional study was conducted on 616 parent child pairs of under five children using structured questionnaire and anthropometric measurements. World health organization new growth reference was used to convert height measurements into Z-scores of the height for age indices considering age and sex of the child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
3
9
1
3
Order By: Relevance
“…In the present study, maternal education was associated with child stunting, which is a similar finding to other reports ( 40 , 41 , 43 53 ) . This could be explained by the close interaction between mother and child, and the role of formal education in awareness creation regarding hygiene, dietary diversity, child feeding practice and the capability of decision making.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, maternal education was associated with child stunting, which is a similar finding to other reports ( 40 , 41 , 43 53 ) . This could be explained by the close interaction between mother and child, and the role of formal education in awareness creation regarding hygiene, dietary diversity, child feeding practice and the capability of decision making.…”
Section: Discussionsupporting
confidence: 93%
“…Sex and regional disparities exist in child malnutrition. In present study, we found that the prevalence of child stunting, wasting, overweight, and obesity were higher among boys than girls in China, which is in accordance with the worldwide nutrition trends based on 2416 population-based measurement studies [24], as well as the studies in European [25,26], American [27], African [28,29], and Asian [30][31][32][33] countries. Consistent with results from other studies [34,35], we found girls have a higher prevalence of underweight in China.…”
Section: Discussionsupporting
confidence: 88%
“…Nine studies were from Amhara [ 26 , 42 , 65 , 76 , 79 , 80 , 84 , 86 , 89 ] and SNNP regions [ 55 , 58 , 60 , 67 , 73 , 75 , 78 , 82 , 83 ]. Studies from Oromia Region ( n = 7) [ 25 , 56 , 59 , 66 , 71 , 77 , 87 ], Tigray Region( n = 3) [ 64 , 69 , 70 ], Somalia Region, Ethiopia ( n = 2) [ 57 , 74 ], Benishangul-Gumz Region ( n = 1) [ 88 ], and Afar Region ( n = 2) [ 68 , 81 ], and six studies were nation-based [ 61 , 62 , 72 , 85 , 90 , 91 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%